Percepções de ganhos para os empregados na gestão por competências:um estudo de caso - Hansch, Rosalice Marília (2008)
Based on the assumption that the Management of People by Competencies should add economic value to the organization and social value for individuals, the present research investigates with the employees of a company the gains brought in their professional and personal life by the implemented model in the organization in which they work. To achieve this objective, a qualitative case study was carried out in a public sector company, which has for more than five years a competency management system, covering all subsystems (selection, training, remuneration, performance evaluation and career ) to 100.0% of the employees. In a "before and after" process of the competency management system, the research was carried out by means of a questionnaire and interview. In order to measure employee gain, the categories and subcategories of social gain defined in the doctoral thesis of Amyra Sarsur, 2007. The results of this research indicate that, in the employee's perception, three subcategories stand out as social gain: development, conceptual understanding of the organization and self-development.The importance of the research is made due to the increasing adoption of this model of people management by the Brazilian companies and the absence of research that investigates the employee gains with the Management by Competencies.